1996
DOI: 10.1111/j.1399-0039.1996.tb02525.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR, DQ genotypes of celiac disease patients and healthy subjects from the West of Ireland

Abstract: Celiac disease (CD) has one of the strongest class II HLA associations of any human illness. We used DNA-RFLP typing to study the class II HLA genotypes of celiac disease patients from the West of Ireland, the geographic area with the highest rate of celiac disease in the world. We confirmed the high frequency of HLA-DR3 in this population, and we were also able to demonstrate the additional risk of developing celiac disease imparted by HLA-DR7. This was done by clearly distinguishing DR7,DQ2 haplotypes from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 28 publications
4
14
0
1
Order By: Relevance
“…These findings agree with other studies in European populations, e.g. Ireland, where Michalski et al [21] reported 71% of DQB1 02* positive CD cases. In our study, the DQB1 0201 frequency was slightly lower than in Finland, investigated by Polvi et al [28], where all the CD patients with both, silent and symptomatic forms, showed the DQB1 0201 allele.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings agree with other studies in European populations, e.g. Ireland, where Michalski et al [21] reported 71% of DQB1 02* positive CD cases. In our study, the DQB1 0201 frequency was slightly lower than in Finland, investigated by Polvi et al [28], where all the CD patients with both, silent and symptomatic forms, showed the DQB1 0201 allele.…”
Section: Discussionsupporting
confidence: 82%
“…Thirty celiac children, 13 boys (case number 1Ϫ13) and 17 girls (case number [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], were studied in the Paediatrics and Microbiology (Immunology Laboratory) Departments of the Universitary Clinic Hospital "Lozano Blesa" in Zaragoza. All these patients were diagnosed according to the criteria established in 1990 by the European Society for Paediatric Gastroenterology and Nutrition (ESPGAN) [12].…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The remainder possess either HLA DQA1*05 or HLA DQB1*02, or express HLA DQ8 encoded by alleles DQA1*03 and DQB1*0302. 5,6 HLA DQ2 and DQ8 are within haplotypes that are also associated with other autoimmune conditions, such as type-1 diabetes mellitus, [7][8][9] autoimmune thyroid disease, [10][11][12] primary biliary cirrhosis, 13 Addison's disease, Sjogren's syndrome and autoimmune hepatitis, 14 although such an association has not always been found. 15,16 A genome wide association study identified non-HLA genes associated with CD.…”
Section: Geneticmentioning
confidence: 99%
“…Furthermore, a solitary case report has shown that the cell-mediated inflammatory response to the HCV may involve T cells restricted to human leukocyte antigen (HLA)-DQ2, the class II HLA allele linked to celiac disease. 15 Hepatitis C virus is a blood-borne pathogen, which is the most common cause of posttransfusion hepatitis worldwide. Blood transfusion in many of patients with celiac disease for anemia might have led to HCV infection.…”
Section: Discussionmentioning
confidence: 99%